The Relationship of Professional Competence of Physical Education Sport and Health Teachers to the Implementation of the 2013 Curriculum of Physical Education, Sport and Health in Elementary Schools in Tambaksari District - Muji Tri Handoyo; Anung Priambodo; Noortje Anita Kumaat (Britain International for Academic Research (BIAR) Publisher, 2020)
The study aims to determine the relationship of PJOK teachers professional competence to the implementation of the 2013 PJOK curriculum in elementary schools in Tambaksari sub-district. This research is a descriptive correlation study, which is the subject of research is all PJOK teachers in Tambaksari sub-district, amounting to 42 teachers. In collecting data using two questionnaires, namely (1) questionnaire to find out the professional competence of PJOK teachers and (2) questionnaire to find out the implementation of the 2013 PJOK curriculum, which was made through Google and distributed through the PJOK teachers working grup (KKG) Tambaksari sub-district. Analysis of the data used is descriptive analysis to determine the percentage of respondents anwers, norm reference assessment (PAN) to determine score criteria, product moment correlation analysis and coefficient of determination. Based on data analysis, obtained the professional competency value of PJOK teachers in Tambaksari district with an average of 40.21 in the classification is quite good, the value of the implementation of the 2013 PJOK curriculum in Tambaksari district with an average of 44.38 in the category is quite good, and correlation coefficient of 0.358 with a significance of 0.020, when compared with r table then r_(count) > r_tabel (0.358 > 0.304) so that it can be concluded that there is a significant relationship between the professional competence of PJOK teachers and implementation of the 2013 PJOK curriculum in elementary schools in Tambaksari sub-disrict. Calculation of the coefficient of determination of 12.82% which means professional competence can affect the implementation of 12.82% and 87.18% influenced by other factors.